Reshaping the World Rethinking Borders - Castañeda, Ernesto (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This volume provides information and analyses to better grasp the social implications of geographical borders as well as the individuals who travel between them and those who live in border regions. Sociologists, anthropologists, philosophers, linguists, and scholars of international relations and public health are just some of the authors contributing to Rethinking Borders. The diversity in the authors' disciplines and the topics they focus on exemplify the intricacies of borders and their manifold effects. This openness to so many schools of thought stands in contrast to the solidification of stricter borders across the globe. The contributions range from case studies of migrants' sense of belonging and safety to theoretical discussions about migration and globalization, from empirical studies about immigrant practices and exclusionary laws to ethical concerns about the benefits of inclusion. It is timely that this collective work is published in the middle of a pandemic that has affected every single part of the world. Unprecedented border closures and stringent travel restrictions have not been enough to contain the virus entirely. As COVID-19 shows, diseases, ideas, and xenophobic and racist discourses know no borders. Plans that transcend borders are vital when dealing with global threats, such as climate change and pandemics.